The impact of foliar fertilization on the nectar production and apicultural value of sunflower (Helianthus annuus l.) - Fazekas, Csaba; Péntek, Attila (GEORGIKON FOR AGRICULTURE, 2016)
Beside black locust (Robinia pseudoacacia) the sunflower is the second most important bee pasture in Hungary. New species and hybrids are generally considered as the sources for different honey flow of the nectariferous plant. However, the quantity and quality of the nutrition supply of the growing area can more effectively influence the honey flow of sunflower than the genetic potential of the crop. From the agro-technical point of view the nectar production of sunflower cannot be increased through the enlargement of the growing area but by increasing the nectar production in our dissertation. We analysed the correlation between the nectar production and the nutrition supply of the crop in near Mocsa (47°40’37,9"N 18°10’52,0"E). We observed that the essential micro- (Zn and Cu), and macro-elements (Mg and Ca) applied as foliar fertilizers increased the quantity of nectar production. Foliar fertilizers of applied compounds (Zn(OH)2 + ZnCO3, Cu(NH3)4, MgCO3, CaCO3) were produced from industrial by-products of high purity. We used ICPAES analytical measuring method to measure the exact active substance. Compared to the control foliar fertilizer agents induced positive quantitative change in one floret in the dosage range of 0.086–0.341 mg/flower and in the average of three sample taking days (n = 864). We examined the data with non-parametric significance method. Compared to the control (p < 0.05) every sunflower hybrid showed higher nectar production due to tetramine-copper application.